2013
DOI: 10.1099/mic.0.065532-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli CS21 pilus contributes to adhesion to intestinal cells and to pathogenesis under in vivo conditions

Abstract: Colonization surface antigens (CSs) represent key virulence-associated factors of enterotoxigenic Escherichia coli (ETEC) strains. They are required for gut colonization, the first step of the diarrhoeal disease process induced by these bacteria. One of the most prevalent CSs is CS21, or longus, a type IV pili associated with bacterial self-aggregation, protection against environmental stresses, biofilm formation and adherence to epithelial cell lines. The objectives of this study were to assess the role of CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…This suggested that anti-CS21 and anti-LngA immune responses may inhibit CS21-mediated ETEC binding to intestinal cells and may block gut colonization. Evidence that anti-LngA antibodies inhibited CS21-dependent ETEC adherence to intestinal cells was previously demonstrated in vitro (Guevara et al 2013). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggested that anti-CS21 and anti-LngA immune responses may inhibit CS21-mediated ETEC binding to intestinal cells and may block gut colonization. Evidence that anti-LngA antibodies inhibited CS21-dependent ETEC adherence to intestinal cells was previously demonstrated in vitro (Guevara et al 2013). …”
Section: Discussionmentioning
confidence: 74%
“…A 16-gene cluster, essential in the biosynthesis of CS21, includes structural and regulatory genes (Gomez-Duarte et al 2007). The CS21 structural subunit gene lngA encodes a 22 kDa mature protein implicated in CS21-mediated ETEC specific adherence to intestinal cells (Guevara et al 2013). CS21 also mediated bacterial self-aggregation believed to promote resistance to environmental stress factors (including antimicrobials) (Clavijo et al 2010, Cruz-Córdova et al 2014, Guevara et al 2013, Mazariego-Espinosa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…24 In their experimental animal model, Guevara and others confirmed the role of CS21 in the pathogenesis of ETEC diarrhea. 25 More recently, the ETEC isolates with CS21 has been linked with self-aggregation, biofilm formation, and adherence to intestinal cells among Bangladeshi children with diarrhea. 26 Apart from CS21, the other two CFs that were more frequently expressed were CS6 (25%) and CS3 (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Guevara et al recently investigated one colonization factors, the CS21 pilus, and its role in adherence and pathogenesis in vivo (29). They found that ETEC CS21 (Longus) adherence to primary intestinal cells was inhibited by anti-LngA sera and the purified LngA protein.…”
Section: Enterotoxigenic E Coli (Etec)mentioning
confidence: 99%